2018
DOI: 10.1021/acs.energyfuels.8b00371
|View full text |Cite
|
Sign up to set email alerts
|

Ash Fusion Characteristics and Transformation Behaviors during Bamboo Combustion in Comparison with Straw and Poplar

Abstract: In this work, the bamboo ash fusion and sintering characteristics were studied to evaluate its potential application in combustion for the production of heat and power. Poplar and wheat straw were used in the experimental test as the reference fuels for comparison. Standard ash fusion tests and ash sintering tests were carried out at elevated temperatures. The results indicate that bamboo has a low ash melting temperature of 862 °C, much lower than that of poplar. In spite of the high K content in bamboo ash, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 37 publications
(85 reference statements)
1
10
0
Order By: Relevance
“…The study findings confirm that woody biomass produced from poplar does not undergo severe sintering during the combustion process [42]. This has been shown to be related to the high melting temperature of the ash and to the presence of large amounts of refractive compounds in the ash [43]. Nonetheless, the present findings show that K/Ca ratios may be higher than previously reported for poplar [44].…”
Section: Slagging Risk Indeces and Observed Slaggingsupporting
confidence: 88%
“…The study findings confirm that woody biomass produced from poplar does not undergo severe sintering during the combustion process [42]. This has been shown to be related to the high melting temperature of the ash and to the presence of large amounts of refractive compounds in the ash [43]. Nonetheless, the present findings show that K/Ca ratios may be higher than previously reported for poplar [44].…”
Section: Slagging Risk Indeces and Observed Slaggingsupporting
confidence: 88%
“…Ash has an important implication on harvesting or industrial operations. Bamboo ash content varies according to species and management, equal to or less than 1% [22,23]. In the present study, where different bamboo ages were sampled, a higher ash content found is still within the limits described [24,25].…”
Section: Discussionmentioning
confidence: 45%
“…Also, increasing age led to a decrease in N, P, K, and Ca and increased Mg concentration. The relatively high value of P stands out for being considered an essential element due to its characteristic of facilitating the formation of high melting point K-Ca / Mg phosphate compounds, which, combined with the low ash content, would characterize bamboo as a promising biofuel for not presenting severe sintering at temperatures below 1000 °C [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silica, potassium oxide, magnesium oxide, and lime compounds were predominantly observed in the samples. The abundance of K in MSLA together with the high Si content favors the formation of alkali-rich silicates and thus decreases the ash melting temperature (Zhu et al 2018). Meanwhile, the contents of refractory species Mg, Ca, Fe, Al, Si, S, and P were nearly constant or slightly increased with temperature.…”
Section: Chemical Compositionmentioning
confidence: 99%